Optimalisasi Pendayagunaan Dana Zakat Untuk Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Melalui Program Bantuan Modal Usaha di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Jember - Dani, Risqi Arum; Nur, Siti Khayisatuzahro; Bashori, Dhofir Chatur (Jurnal Manajemen dan Ilmu Administrasi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic growth, including in Jember Regency. However, limited access to capital and low human resource quality remain major obstacles to their development. The National Amil Zakat Agency (BAZNAS) of Jember Regency seeks to address these issues through a business capital assistance program based on productive zakat. This study aims to analyze the management of productive zakat, the optimization of zakat fund utilization for MSME development, and BAZNAS’s strategies in overcoming challenges within the business capital assistance program. A descriptive qualitative approach was used, with data collected through interviews, observations, and documentation. Data analysis was conducted using the SWOT method to identify strengths, weaknesses, opportunities, and threats in the program’s implementation. The findings indicate that BAZNAS Jember has implemented a structured productive zakat management system, including planning stages (strategic and annual work plans), fund collection (both online and offline), and selective distribution. The business capital assistance program has increased the productivity of beneficiary MSMEs, although some issues remain, such as limited funding amounts and suboptimal mentoring. The development strategy, formulated through SWOT analysis, includes enhanced mentoring, expanded stakeholder collaboration, and stronger monitoring systems. Recommendations include increasing the amount of financial assistance, hiring more support staff, and expanding the program to other potential MSME sectors. Thus, this research provides practical contributions to BAZNAS in improving the effectiveness of productive zakat programs and theoretical contributions to sharia economic literacy concerning zakat-based MSME empowerment.